Pengaruh Sistem Pengendalian Intern, Sistem Informasi Akuntansi, Dan Komitmen Organisasi Terhadap Akuntabilitas Pengelolaan Alokasi Dana Desa Pada Desa-Desa di Kecamatan Kupang Tengah - Abdon Lodowik Tasesab; Yohanes Demu; Maria Prudensiana L. Muga (Jurnal Riset Akuntansi, 2025)
This research aims to determine the influence of the internal control system, accounting information system, and organizational commitment on the accountability of village fund allocation management in villages in the Kupang Tengah District. The data used in this research are primary and secondary data. The data obtained in this research were collected through questionnaires distributed directly to all village officials in the Kupang Tengah District. This study uses a Quantitative approach with a saturated sampling technique. The data analysis technique used is descriptive statistical analysis, validity test, reliability test, normality test, and hypothesis testing. The analysis tool used is Statistical Package for the Social Sciences 23 (SPSS 23). The results of this study indicate that there is a significant influence of the internal control system, accounting information system, and organizational commitment on the accountability of village fund allocation management.